2014
DOI: 10.1177/1403494813516831
|View full text |Cite
|
Sign up to set email alerts
|

Falls and comorbidity: The pathway to fractures

Abstract: The results suggest that the overall reduction in fractures can be explained by reduction in falls related comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 33 publications
6
15
0
Order By: Relevance
“…Recent studies have suggested that reduction in fractures can be explained by reductions in falls-related comorbidity [45]. Data from Estonia are in line with this hypothesis: over the period of this study, the life expectancy at 65 in Estonian women increased from 18.1 to 20.3 years (2.2 years) [46], indicating an improved general health and prevention and treatment of chronic diseases.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have suggested that reduction in fractures can be explained by reductions in falls-related comorbidity [45]. Data from Estonia are in line with this hypothesis: over the period of this study, the life expectancy at 65 in Estonian women increased from 18.1 to 20.3 years (2.2 years) [46], indicating an improved general health and prevention and treatment of chronic diseases.…”
Section: Discussionsupporting
confidence: 69%
“…We observed positive associations between all disease categories and hip fracture, a pattern reported by others, albeit for a smaller range of diseases, in relation to falls [11] and hip fracture [21]. The threefold increased risk of hip fracture associated with mental and behavioral disorders, the most prevalent of which are disorders caused by psychoactive substances, mood disorders, schizophrenia and dementia, is in accordance with the twofold to threefold increased risk observed in previous cohort studies [14, 21].…”
Section: Discussionsupporting
confidence: 85%
“…The threefold increased risk of hip fracture associated with mental and behavioral disorders, the most prevalent of which are disorders caused by psychoactive substances, mood disorders, schizophrenia and dementia, is in accordance with the twofold to threefold increased risk observed in previous cohort studies [14, 21]. Dementia and hip fracture share several predisposing and intermediate risk factors, such as advanced age, gait impairments and increased risk of falls [27].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nutritional lifestyle changes as calcium and vitamin D supplementation may also contribute to the decrease in hip fracture incidence, especially amongst elderly subjects; however, there is no evidence of an increase of vitamin D intake in Europe [34,35]. Reduction of fall-related comorbidities [36] and prevention of falls may also explain the decrease incidence. Studies showed that the most effective strategies to decrease fall risk in community-living elderly include regular physical training and modification of the fall risk factors: wearing antislip shoes, reducing psychotropic medication and polymedication, vitamin D supplementation, and cataract surgery [37].…”
Section: Potential Explanations Of the Changesmentioning
confidence: 98%